Antibody persistence and safety after heterologous boosting with orally aerosolised Ad5-nCoV in individuals primed with two-dose CoronaVac previously: 12-month analyses of a randomized controlled trial - Lairun Jin; Rong Tang; Shipo Wu; Xiling Guo; Haitao Huang; Lihua Hou; Xiaoqin Chen; Tao Zhu; Jinbo Gou; Jin Zhong; Hongxing Pan; Lunbiao Cui; et al. (Emerging Microbes and Infections, 2023)
Antibody persistence and safety up to 12 months of heterologous orally administered adenovirus type-5 vector-based COVID-19 vaccine (Ad5-nCoV) in individuals who were primed with two-dose inactivated SARS-CoV-2 vaccine (CoronaVac) previously, has not been reported yet. This randomized, open-label, single-centre trial included Chinese adults who have received two-dose CoronaVac randomized to low-dose or high-dose aerosolised Ad5-nCoV group, or CoronaVac group. In this report, we mainly evaluated the geometric mean titres (GMTs) of neutralizing antibodies (NAbs) against live wild-type SARS-CoV-2 virus and omicron BA.4/5 pseudovirus at 12 months after the booster dose and the incidence of serious adverse events (SAEs) till month 12. Of 419 participants, all were included in the safety analysis and 120 (28.64%) were included in the immunogenicity analysis. Serum NAb GMT against live wild-type SARS-CoV-2 was 204.36 (95% CI 152.91, 273.14) in the low-dose group and 171.38 (95% CI 121.27, 242.19) in the high-dose group at month 12, significantly higher than the GMT in the CoronaVac group (8.00 [95% CI 4.22, 15.17], p < 0.0001). Serum NAb GMT against omicron BA.4/5 pseudovirus was 40.97 (95% CI 30.15, 55.67) in the low-dose group and 35.08 (95% CI 26.31, 46.77) in the high-dose group at month 12, whereas the GMT in the CoronaVac group was below the lower limit of detection. No vaccine-related SAEs were observed. Orally administered aerosolised Ad5-nCoV following two-dose CoronaVac priming has a good safety profile and is persistently more immunogenic than three-dose CoronaVac within 12 months after the booster dose.Trial registration: ClinicalTrials.gov identifier: NCT05043259..